Rancang Bangun Sistem Pendaftaran Online Kegiatan BEM Fasilkom Unsika Berbasis Website - Putri Fisichella Chasannove; Arip Solehudin; Asep Jamaludin (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The Student Executive Board (BEM) of the Faculty of Computer Science at Universitas Singaperbangsa Karawang (Unsika) currently relies on Google Forms to manage event registrations, causing participant data to be scattered across multiple documents, increasing the risk of duplicate records, and making participant verification, quota management, and report preparation less efficient. This study aims to design and develop a website-based online registration system that centralizes participant data management, supports participant verification, prevents duplicate registrations, and improves the management of BEM activities. The research employed the System Development Life Cycle (SDLC) using the Waterfall model, which consists of requirements analysis, system design, implementation, and testing stages. The system was developed using PHP Native and MySQL as the database management system. Functional testing was conducted using the Black Box Testing method to verify that all system features met user requirements. The results indicate that the developed system successfully provides user registration, authentication, event management, participant registration, participant data management, participant data export, and registration history within an integrated platform. The testing results demonstrate that all system functions operated as expected, indicating that the system is feasible for implementation. Therefore, the proposed system improves administrative efficiency, simplifies participant data management, and supports the digitalization of BEM activity services at the Faculty of Computer Science, Universitas Singaperbangsa Karawang.